Synthesis and Properties of Nd-doped Bi4Ti3O12 using the soft combustion technique - Al-Amani, Umar (Nova Science, 2012)
Nd-doped Bi4Ti3O12 ceramics, Bi4-xNdxTi3O12 (BNT, x = 0, 0.25, 0.50, 0.75 and 1), were prepared using a soft combustion technique and their phase, structure, thermal behavior, grain morphology, dielectric and ferroelectric properties were investigated. The single phase of BIT was successfully obtained at different synthesis temperature, just after combustion took place at 450oC. The thermal analysis confirmed the phase formation with corresponding temperature. The single phase of BIT was also obtained with different Nd doping. It was also shown that Nd doping had a significance change in Raman and Fourier Transform Infrared spectroscopy (FTIR) spectra. Further increase the sintering temperature at 900oC did not show the presence of secondary phase in X-ray diffraction (XRD) pattern. The average grain length and width decreased with Nd content. The Curie temperature of BNT also reduced to 434oC. The remanent polarization, 2Pr and coercive field, 2Ec of BNT were higher than BIT, whereby the BNT 075 ceramics exhibited the maximum 2Pr and 2Ec values of about 18.4 μC/cm2 and 100.6 kV/cm, respectively.